2010
DOI: 10.1016/j.pepi.2010.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial paleosecular variation of the geomagnetic field from 0 to 3 Ma lavas from the Galapagos Islands

Abstract: a b s t r a c tComplete progressive thermal demagnetization of nearly 400 oriented samples from 58 sites (lava flows) from the Galapagos Islands of Santa Cruz, San Cristobal and Floreana provide data for the statistical characterization of the time-averaged geomagnetic field near the Equator for the past few million years. Estimates of VGP dispersion due to paleosecular variation range from 9.2 • to 11.8 • depending on site selection criteria; our preferred estimate based on 64 site VGPs (51 accepted from this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 42 publications
2
30
0
1
Order By: Relevance
“…Previous alternating field (AF) (16) and thermal demagnetization (TD) (13) studies showed shallow average paleomagnetic directions (AF mean I = 1.9°± 3.0°; TD mean I = 2.3°± 3.0°) from 51 lava sites, which agree with the GAD hypothesis. Like many lava samples that have been studied, most of the Galapagos lavas have saturation-remanent to saturation-induced magnetization ratios between 0.1 and 0.3 (13), which is consistent with a mixture of SD and MD properties (17). We also conducted additional comprehensive rock magnetic studies, which suggest most of the Galapagos lavas are good candidates for MD-corrected paleointensity experiments (SI Appendix, Figs.…”
Section: Significancesupporting
confidence: 55%
“…Previous alternating field (AF) (16) and thermal demagnetization (TD) (13) studies showed shallow average paleomagnetic directions (AF mean I = 1.9°± 3.0°; TD mean I = 2.3°± 3.0°) from 51 lava sites, which agree with the GAD hypothesis. Like many lava samples that have been studied, most of the Galapagos lavas have saturation-remanent to saturation-induced magnetization ratios between 0.1 and 0.3 (13), which is consistent with a mixture of SD and MD properties (17). We also conducted additional comprehensive rock magnetic studies, which suggest most of the Galapagos lavas are good candidates for MD-corrected paleointensity experiments (SI Appendix, Figs.…”
Section: Significancesupporting
confidence: 55%
“…This suggests that some of the contribution to shallow bootstrapped mean inclination, particularly in Area A, is from large scatter of the directions; however, even filtering the data does not produce a mean direction with a steeper inclination similar to the expected GAD inclination. Southward motion of the Nazca Plate over the last ∼3 Ma contributes to shallower inclinations; however, the contribution of ∼0.6°change in latitude suggested from paleomagnetic data from the Galapagos Islands [Kent et al, 2010], corresponds to ∼0.8°shallower inclinations and is not sufficient to explain the significant deviation observed. The rotation about a horizontal axis parallel to Pito Deep Rift is one of the only geologically reasonable means of creating more shallow inclinations.…”
Section: Shallow Bootstrapped Mean Remanence Directionsmentioning
confidence: 73%
“…Standard deviation of inclination is equal to the α 95 of the mean paleomagnetic direction. Calculation of inclination anomaly from Galapagos Islands was made assuming the location of Fernandina Island (latitude −0.37º) as the position of the hotpot in order to account for the movement of the Nazca plate [ Kent et al ., ].…”
Section: Resultsmentioning
confidence: 99%